2002
DOI: 10.1055/s-2002-35753
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Complicated Skull Base Defects Utilizing Free Tissue Transfer

Abstract: We managed five patients with large skull base defects complicated by complex infections with microvascular free tissue transfer. The first patient developed an infection, cerebrospinal fluid (CSF) leak, and meningitis after undergoing a translabyrinthine resection ofan acoustic neuroma. The second patient had a history of a gunshot wound to the temporal bone, with a large defect and an infected cholesteatoma that caused several episodes of meningitis. The third through the fifth patients had persistent CSF le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…[5][6][7][8] However, because of the distance between the skull base and the submandibular region, especially when the anterior skull base is accessed via the subcranial approach, vein grafts are often required for the anastamosis of free flaps. 1,9 Hussussian and Reece 10 have reported that the caliber of the STV is insufficient for microvascular anastomosis in scalp reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] However, because of the distance between the skull base and the submandibular region, especially when the anterior skull base is accessed via the subcranial approach, vein grafts are often required for the anastamosis of free flaps. 1,9 Hussussian and Reece 10 have reported that the caliber of the STV is insufficient for microvascular anastomosis in scalp reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Djalilian et al reported five patients with large skull base defects because of complex infections (mainly meningitis but not osteomyelitis). Free tissue transfer, such as myofascial and muscle free flaps, was successfully used for dead‐space management after debridement …”
Section: Resultsmentioning
confidence: 99%
“…The complications of the anterior iliac approach can include prolonged postoperative pain, altered gait, sensory nerve damage, poor scar placement and altered bone contour, delayed healing, herniation of abdominal contents, clicking during walking, ilium fracture, peritonitis, excessive blood loss, and rarely retroperitoneal haematoma . Free and pedicled fat transplants have also been described and are well established in the management of bone defects in cranio‐maxillofacial surgery; however, these procedures are resource intensive, expensive, and limited to specialised centres . In autologous fat transfer, the possible complications appear to be minimal and related to the liposuction technique (like bruising, swelling, haematoma formation, paraesthesia or donor site pain, infection, hypertrophic scarring, contour irregularities, and damage to the underlying structures, eg, because of the intra‐peritoneal or intramuscular penetration of the cannula if fat is harvested from the abdomen) .…”
Section: Discussionmentioning
confidence: 99%
“…Иíòðàîïåðàöèîííàя бèîïñèя, â òîм чèñëå ñîмíèòåëüíых óчàñòêîâ ТÎÃМ, ïðîâåäåíà ó 12 (52%) бîëüíых. Äåфåêòы ТÎÃМ зàêðыâàëè фðàãмåíòàмè aeèðîâîé êëåòчàòêè è ñâåðхó óêëàäыâàëè ïåðåмå-щåííыé ëîñêóò íàäêîñòíèöы â âèäå фàðòóêà [14,23]. Êîñòíыå äåфåêòы íå òðåбóюò зàмåщåíèя.…”
unclassified